ANALISIS EMPIRIS PENGHINDARAN PAJAK DI PERGURUAN TINGGI - Nurhalisa, Icha; Machdar, Nera Marinda (Jurnal Riset Akuntansi & Keuangan, 2025)
Taxes are a source of state income which is used to finance government spending and national development, so taxes have an important role in the development of the Indonesian economy. But taxpayers always want to pay as little tax as possible, whereas for the government taxes are the main source of national income, so Tax Avoidance occurs. This research aims to examine the influence of Love of Money, Religiosity and Gender on Tax Avoidance. The method in this research uses a literature review, namely research that finds theories and analyzes them. This research found that: 1) Love of Money influences Tax Avoidance; 2) Religiosity influences Tax Avoidance and; 3) Gender influences Tax Avoidance